Proceedings of the 3rd International ICST Conference on Body Area Networks 2008
DOI: 10.4108/icst.bodynets2008.2945
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Radio Transmit Power in Wireless Body Area Sensor Networks

Abstract: Emerging body-wearable devices for continuous health monitoring are severely energy constrained and yet required to offer high communication reliability under fluctuating channel conditions. This paper investigates the dynamic adaptation of radio transmit power as a means of addressing this challenge. Our contributions are three-fold: we present empirical evidence that wireless link quality in body area networks changes rapidly when patients move; fixed radio transmit power therefore leads to either high loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…A complete overview about the modeling, tools, and their applications of wireless networks was provided in Haenggi et al (2009). And a number of schemes (Akan et al, 2009;Bulut and Korpeoglu, 2011;Xiao et al, 2008;Quwaider et al, 2010) have been proposed to minimize energy consumption in wireless sensor networks. The feasibility of passive sensor networks was studied in Akan et al (2009) to provide an environment free of energy constraints; however, such a network would require an external RF resource.…”
Section: Introductionmentioning
confidence: 99%
“…A complete overview about the modeling, tools, and their applications of wireless networks was provided in Haenggi et al (2009). And a number of schemes (Akan et al, 2009;Bulut and Korpeoglu, 2011;Xiao et al, 2008;Quwaider et al, 2010) have been proposed to minimize energy consumption in wireless sensor networks. The feasibility of passive sensor networks was studied in Akan et al (2009) to provide an environment free of energy constraints; however, such a network would require an external RF resource.…”
Section: Introductionmentioning
confidence: 99%
“…There is thus an inherent delay between sampling the channel and adjusting the transmit power, which limits the performance of practical schemes. In our earlier work [14] we had proposed practical power control schemes for body area devices. In this section we analyze and evaluate the performance of the "aggressive" scheme in the three scenarios under consideration.…”
Section: Practical Transmit Power Control Schemementioning
confidence: 99%
“…In our earlier work [14] we had proposed dynamic power control as a means of improving the energy performance of body area sensor devices, and validated our proposed algorithms using MicaZ motes. In this work we experiment with the Toumaz Sensium platform and establish the efficacy of dynamic power control for truly-wearable devices which are specifically designed for health monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier paper [8] showed that transmit power control can help body-worn devices save energy with minimal impact on reliability. Our algorithm embedded power control information in acknowledgment packets sent in response to each transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier work [8] motivated the need for dynamic power control by recording extensive trace data, and proposed a power control algorithm for the sensor node. The traces record the RSSI at the base station when packets are sent by the target at 16 different power levels every second.…”
Section: Introductionmentioning
confidence: 99%